Kaiphal (Myrica nagi): A Botanical Origin Drug (Dawa) of Unani Medicine for Prevention and Treatment of Common Disorders - AHMAD, KALEEM; Quamri, Mohd Aleemuddin (Journal of Drug Delivery and Therapeutics, 2023)
Myrica nagi is a celebrity medicinal plant that is distributed in sub-Himalayan regions and holds several pharmacological actions and therapeutic effects along with their economic usage. In Unani System of Medicine (USM), it is well known, as Kaiphal and used in the prevention and the management of several common disorders viz. Amraz-i-Riya (Respiratory disease), Amraz-i-Hazam (Gastrointestinal disease), Amraz-i-Aasab (Nervine disease), and Amraz-i-Bawl (genitourinary disease). Recent clinical studies evaluate that the Kaiphal consist of numerous phytoconstituents viz. tannins, flavonoids, phenolic acids, terpenes, glycosides, amino acids, steroids, and volatile oils. These phytoconstituents are responsible for varieties of pharmacological actions viz. Anti-inflammatory, Anti-Oxidant, Anti-Allergic, Anti-helminthic, Neuroprotective, Nephroprotective, Anti-hypertensive, Anticancer, and Anxiolytic. Conventionally, different parts of Kaiphal are used in asthma, allergic disorder, inflammatory diseases, neurological disorders, renal disease, and cancer. The physicians of USM described properties and therapeutics uses of Kaiphal but data on safety and efficacy are limited and also lack of attraction of researcher toward a preclinical and clinical trial. Therefore, this review updated the knowledge about pharmacological and therapeutic effects, ethnomedicinal uses, adverse effects, prevention and treatment of common disorders and also focused on future research in the prospective era. Keyword: Kaiphal, Myrica nagi, USM, Phytoconstituents, Asthma